TECHNOLOGY OF INFORMATION COMPETENCE FORMATION BASED ON THE PREVENTION OF VIRTUAL ADDICTION IN STUDENTS - Yoziyeva Umida Lutfullayevna (American Journals, 2023)
The article deals with the need to protect primary school pupils against the threat of harmful information, the negative effects of the information threat, and the pedagogical conditions for prevention.
Keywords: information society, education, media violence, intellectual, risk, information threat, culture of information consumption, mental development